L’oekoumène agricole au Lac-Saint-Jean - Biays, Pierre (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1962)
Two maps of the agricultural ecumene of the Lake Saint-Jean region are presented, the first showing the extent of cleared land as determined from air photos and the second indicating the present legal status of all surveyed parcels of land. The present land use is discussed in relation with the physical environment and the history of colonisation. In some areas the limits of the agricultural ecumene correspond to the contact between the alluvium-blanketed lowland and the surround-ing Precambrian upland ; in other areas the system of land allocation bas determined the limits of the ecumene, for the advance of colonisation was often brought to a halt by the establishment of for est reserves on Crown lands. The pioneer fringe municipalities of Saint-Ludger-de-Milot and Lac-Bouchette are located in such regions of arrested settlement.The writer concludes that throughout the Lake Saint-Jean area the lands presently under cultivation are bordered by territories unsuitable for farm settlement — consequently, it appears that the agricultural ecumene of the region bas attained its furthest extension.